An empirical investigation of scheduling performance criteria - De Snoo, Cees; Van Wezel, Wout; Jorna, René J. (Journal of Operations Management, 2011)
Abstract Planning and scheduling significantly influence organizational performance, but literature that pays attention to how organizations could or should organize and assess their planning processes is limited. We extend planning and scheduling theory with a categorization of scheduling performance criteria, based on a three‐stage survey research design. Particularly, the results show that, next to schedule quality, the planning process factors timeliness, flexibility, communication, and negotiation are important performance criteria, and especially so in organizations that are faced with high levels of uncertainty. The results suggest that organizational and behavioral aspects of planning and scheduling cannot be mitigated with advanced models and software that solely focus on good schedules. Rather, high quality schedules and high quality scheduling processes need to be facilitated simultaneously to attain high planning and scheduling performance.